English teaching and “RSBI” schools - Subekhi Hadi Purnomo (Jurnal Linguistik Terapan, 2011)
Bilingual education programs in Indonesia are becoming popular and many parents are very keen on sending their children to these bilingual classes. Bilingual classes which are offered by many schools, which usually have the label of RSBI or SBI have not been running without criticisms. Critics ask about the effectiveness of the bilingual learning. Questions are also raised about the issues of high rates of school fee and the English competence of the teachers. Nevertheless, parents believe that bilingual classes can provide their children with better education because these classes are equipped with better facilities and technologies and more qualified teachers. Then, what can be the trend of the bilingual classes in the future?